Does Surface Topography Improve Electrochemical Behavior of Ti–6Al–4V Alloy in Different Saliva pH Levels? - Faverani, Leonardo Perez [UNESP]; Fogaça, Juliana Ferreira [UNESP]; Machado, Thiago [UNESP]; Silva, Ebele Adaobi [UNESP]; Barão, Valentim Adelino Ricardo; Assunção, Wirley Gonçalves [UNESP] (Springer Nature, 2015)
The objective of this study was to evaluate the corrosion kinetics and microstructural change of a Ti–6Al–4V alloy with machined and treated surfaces (sandblasted with aluminum oxide or double acid-etched) at three salivary pH levels. For an electrochemical test (n = 5), open-circuit potential and electrochemical impedance spectroscopy analyses were conducted in artificial saliva at pH 3, 6.5, and 9 in the three types of Ti–6Al–4V surfaces. The capacitance (CPE) and the polarization resistance (Rp) of the titanium oxide layer were determined. Disk surfaces were characterized using scanning electron microscopy, atomic force microscopy, and profilometry, which provided the surface roughness (Ra) of the disks before (baseline) and after the electrochemical test. The corrosion parameters were compared by two-way ANOVA. One-way ANOVA was applied for analyzing Ra values of the specimens before and after the electrochemical process. For results that were statistically significant, the Tukey HSD test was used. The level of significance used for all tests was 0.05. The highest value of Rp was observed on disks with machined surfaces and treated with double acid-etching (p = 0.264), which was independent of the salivary pH level. Sandblasting decreased the Rp of Ti–6Al–4V at all pH levels (p < 0.05). The machined surface showed the lowest CPE, followed by the surfaces treated with double acid-etching, and the highest values were observed for the sandblasting (p < 0.05), which were all independent of the pH. It was concluded that a higher corrosion process was observed in the Ti–6Al–4V alloys surface sandblasted with aluminum oxide. Acidic pH tended to reduce total impedance values. Acid-etching may be a suitable treatment for dental implants as it provides good corrosion resistance and increased contact area for bone adhesion.
Keywords: Corrosion; pH; Saliva; Titanium